The knowledge economy is an essential pillar for increasing exports in Republic of Korea and Iraq: A comparative analysis for the period 2003- 2018 - Ali Owish, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Mankind has witnessed economic patterns and various and multiple types of knowledge, innovation, renewal and development since the beginnings of the industrial revolution in Europe and England in particular and the gradual transformation from the traditional style to the pattern of knowledge economy. This pattern has become a reality and the concept imposes itself strongly to make its way in a changing world accelerated by innovations and knowledge renewal in all countries including developing, as it is an organization for contemporary aspects of life and societies. We have no choice but to respond quickly to its requirements to achieve comprehensive development and raise economic growth rates by increasing the volume of merchandise exports and demanding the implementation of a strategy to replace exports. This research comes to find out the reality of this economy in Iraq by comparing it with a pioneering experience from one of the global experiences of one of the countries that has taken great steps towards growth that is the Republic of Korean experience to stand shocked against numbers, data and indicators that were produced by the study. Nevertheless, Iraq possesses many of the possibilities of economic, physical, natural and human constituents to raise the knowledge economy indicators in Iraq in order to make it moving towards the growth economically, cognitively and socially for the purpose of achieving the sustainable human development goals and getting rid of the rentier, economic and social phenomena such as poverty, deprivation, ignorance, unemployment, corruption and others.